Pengembangan Perangkat Pembelajaran Model Anchored Instruction Berbantuan Video Untuk Meningkatkan Penguasaan Konsep Fisika Peserta Didik - Lalu Romi Setiawan; Sutrio Sutrio; Muhammad Taufik (Indonesian, 2020)
Physics learning in schools tends to use conventional methods and has not used learning media optimally. This has an impact on the low learning outcomes of physics, which reflects the students' low mastery of physics concepts. Therefore, a video-assisted anchored instruction model was developed. This research aims to produce a video-assisted anchored instruction model to improve students' mastery of physics concepts. The research design used is to adapt the 4D model, namely define, design, develop, and disseminate. The research stage is limited to the develop stage. Products developed in the form of a syllabus, lesson plans (RPP), student worksheets (LKPD), concept mastery test instruments, and learning videos. The data collection technique used a validation questionnaire to determine the validity and reliability of the product. The results of the validity were analyzed using the calculation of the Content Validity Ratio (CVR), and the Content Validity Index (CVI), and the reliability of the product was calculated using a Percentage Agreement (PA). The results showed that the CVI value was 1 (very good) for all products developed and the entire product had an average PA greater than 75% in the reliable category. Based on these results, it can be concluded that the learning device developed is feasible to be tested on class X students to improve students' mastery of physics concepts.